INTEGRATING BASIC SYNTAX LEARNING TO IMPROVE ENGLISH WRITING ACCURACY AND GRAMMATICAL COMPREHENSION OF 11TH GRADE STUDENTS - Bahagia Saragih; Barli Kifli; Ahdan Labarata Sagala; Ashlah Nurshadiqah; Jessi Keysia Simangunsong; Laura Isabella Lumbantobing; M. Alif Putra Panjaitan; Meilani Simatupang (STKIP Subang, 2026)
This study aims to investigate the relationship between basic syntax mastery and English writing accuracy among Indonesian senior high school students, identify specific syntactic challenges they encounter, and examine how explicit syntax instruction contributes to improved grammatical comprehension in written production. Data were collected from 15 eleventh-grade students at a public senior high school. Sources included a diagnostic syntax test, student essays, and structured questionnaires. A mixed-methods design employed three instruments: a 15-item multiple-choice syntax diagnostic test covering basic sentence structure, parts of speech, phrases, clauses, and sentence types; an essay writing task analyzed for syntactic accuracy using an error classification framework; a student perception questionnaire. Quantitative data were analyzed through descriptive statistics and error frequency calculations; qualitative data underwent thematic analysis. The diagnostic test revealed a mean score of 6.87 out of 15 (45.8%), indicating below-average syntax mastery. Essay analysis showed an average syntactic error rate of 64.4%, with the most frequent errors being incorrect word order (27.3%), sentence fragments from omitted subjects or verbs (22.1%), run-on sentences (19.5%), incorrect conjunction use (17.2%), and tense inconsistency (13.9%). Students demonstrated greater accuracy with simple sentences but struggled significantly with complex structures requiring subordination and clause embedding. Questionnaire responses indicated that 73.3% of students lacked confidence in constructing grammatically accurate English sentences. The findings underscore the critical need for explicit, systematic syntax instruction integrated into EFL writing curricula. Pedagogical strategies including syntactic awareness exercises, sentence-combining activities, and targeted error correction are recommended to bridge the gap between theoretical knowledge and practical writing application.